AI-Assisted Learning with ChatGPT and Large Language Models: Implications for Higher Education - Laato, Samuli; Morschheuser, Benedikt; Hamari, Juho; Bjorne, Jari (Proceedings (IEEE International Conference on Advanced Learning Technologies), 2023)
The recent progress in generative AI models, particularly large language models (LLMs), has brought about a transformation in the field of education. Conversational LLM services, such as Google's Bard and OpenAI's ChatGPT, offer students access to many abilities such as summarization and generation of text and code, and on-demand replies to questions on expert topics. In this paper, we observe ChatGPT to explore how LLM services impact learning and instruction in higher education. First, we mapped the capabilities of the system by reviewing the grey literature on ChatGPT and using the system ourselves for two months. Second, we selected a Bachelor level computer science curriculum from a Finnish university, and examined the impact of ChatGPT on the offered courses. As an outcome of this study, we highlight 13 implications for students' learning in higher education, and discuss the contemporary future of AI-assisted learning in universities and beyond.